Genetic and Clinical Features of Heterotaxy in a Prenatal Cohort - Yi, Tong; Sun, Hairui; Fu, Yuwei; Hao, Xiaoyan; Sun, Lin; Zhang, Ye; Han, Jiancheng; Gu, Xiaoyan; Liu, Xiaowei; Guo, Yong; Wang, Xin; Zhou, Xiaoxue; et al. (Frontiers in Genetics, 2022)
Objectives: Some genetic causes of heterotaxy have been identified in a small number of heterotaxy familial cases or animal models. However, knowledge on the genetic causes of heterotaxy in the fetal population remains scarce. Here, we aimed to investigate the clinical characteristics and genetic spectrum of a fetal cohort with heterotaxy. Methods: We retrospectively investigated all fetuses with a prenatal diagnosis of heterotaxy at a single center between October 2015 and November 2020. These cases were studied using the genetic testing data acquired from a combination of copy number variation sequencing (CNV-seq) and whole-exome sequencing (WES), and their clinical phenotypes were also reviewed. Result: A total of 72 fetuses diagnosed with heterotaxy and complete clinical and genetic results were enrolled in our research. Of the 72 fetuses, 18 (25%) and 54 (75%) had left and right isomerism, respectively. Consistent with the results of a previous study, intracardiac anomalies were more severe in patients with right atrial isomerism than in those with left atrial isomerism (LAI) and mainly manifested as atrial situs inversus, bilateral right atrial appendages, abnormal pulmonary venous connection, single ventricles or single atria, and pulmonary stenosis or atresia. In 18 fetuses diagnosed with LAI, the main intracardiac anomalies were bilateral left atrial appendages. Of the 72 fetuses that underwent CNV-seq and WES, 11 (15.3%) had positive genetic results, eight had definitive pathogenic variants, and three had likely pathogenic variants. The diagnostic genetic variant rate identified using WES was 11.1% (8/72), in which primary ciliary dyskinesia (PCD)-associated gene mutations (CCDC40, CCDC114, DNAH5, DNAH11, and ARMC4) accounted for the vast majority (n = 5). Other diagnostic genetic variants, such as KMT2D and FOXC1, have been rarely reported in heterotaxy cases, although they have been verified to play roles in congenital heart disease. Conclusion: Thus, diagnostic genetic variants contributed to a substantial fraction in the etiology of fetal heterotaxy. PCD mutations accounted for approximately 6.9% of heterotaxy cases in our fetal cohort. WES was identified as an effective tool to detect genetic causes prenatally in heterotaxy patients.